Determination and validation of the contributing factors towards the selection of a B-School - An Indian perspective - Bhattacharjee, Malay; Bandyopadhyay, Gautam; Guha, Banhi; Biswas, Sanjib (Decision Making: Applications in Management and Engineering, 2019)
This study has tried to see what factors do play a significant role in the B-School selection process of an aspirant. The study also would like to see the constituent elements of the factors which come to the mind of the prospective takers, herein, the prospective students. The study pursued here has significant relevance in its purpose as it is one of its kind in this country, and that the rising market demands a study which would be helpful to the pursuant as well as the service providers. The existing management institutions in the country are challenged for their survival. This study intends to make their work easier by identifying the most important factors which the ‘prospective candidates’ look for while selecting their B-School. For this purpose, we have conducted an Exploratory Factor Analysis (EFA) on the responses obtained from a sample of 594 respondents through questionnaire based survey and interviews. Further, in order to ascertain the results, we have done the Confirmatory Factor Analysis (CFA) using Structural Equation Modeling (SEM) approach of the first order type. The result of SEM conforms to that of EFA.